PHOTOVOICE APPROACH AS INVESTIGATION TOOL TO IDENTIFY THE CAUSE OF DISENGAGEMENT OCCURRENCE AMONG APATHETIC ENGLISH LEARNERS - DEBORA Chaterin Simanjuntak (Universitas Suryakancana, 2020)
Student disengagement is an ongoing challenge in college education phenomena. Henceforth, this present article aims to identify the cause of disengagement among apathetic English learners. This study utilized descriptive qualitative research focusing on Photovoice approach, using camera as an investigation tool to identify the causes; it is a methodology that can be adapted to a variety of topics especially for educational setting. Research participants were chosen through purposive sampling; they were asked to take photographs and share their voices on photos they took to represent their current reasons of disengagement. The researcher analyzed the digital images and the accompanying narratives for themes to emerge. Through the analysis process, two main themes emerged from this study regarding reported sources which cause them to disengage form learning. They are: Negative Self-concept and Language Intricacy. The theme of Negative Self-concept contains two categories with four to five labels in each category. Meanwhile the theme of Language Intricacy contains three categories and each category has four labels. With regard to empower the apathetic learners, a theme occurred in the findings which is activity-based program. This theme has two categories and each category has four to five labelsu